Does foreign aid really work? - Riddell, Roger (Oxford : Oxford University Press, 2008)
"In this first-ever attempt to provide an overall assessment of aid, Roger Riddell presents a rigorous but highly readable account of aid, warts and all. Does Foreign Aid Really Work? sets out the evidence and exposes the instances where aid has failed and explains why. The book also examines the way that short-term political interests distort aid, and disentangles the moral and ethical assumptions that lie behind the belief that aid does good. The book concludes by detailing the practical ways that aid needs to change if it is to be the effective force for good that its providers claim it is."--Jacket.
17. The wider impact of non-governmental and civil society organizations : NGO advocacy, lobbying, awareness-raising and campaigning ; Strengthening NGOs and strengthening civil society ; The contribution of NGOs to development : a summing up -- 18. The growth of emergencies and the humanitarian response : Emergencies and disasters : an overview ; The humanitarian aid response -- 19. The impact of emergency and humanitarian aid : Assessing humanitarian aid ; The impact of humanitarian action and humanitarian aid ; Advocacy in humanitarian action ; Emergency and humanitarian aid : a summing up -- Part 4. Towards a different future for aid : 20. Why aid isn't working : Systematic impediments to aid effectiveness : problems caused by donors ; Problems at the recipient end : aid dilemmas ; Conclusion -- 21. Making aid work better by implementing agreed reforms : The discrete individual-donor approach ; The step-change international cooperative approach ; Taking stock -- 22. Making aid work better by recasting aid relationships : Confronting the politics of aid-giving ; Recasting aid relationships ; Making aid work better : addressing five key problem areas ; Bridging the divide between ideas and implementation.
Originally published: 2007.
Includes bibliographical references and index.
Keywords: Economic assistance; Economic assistance -- Evaluation; Economic assistance; Economic assistance -- Evaluation; Evaluation